Quinoline Carbonitriles as Novel Inhibitors for N80 Steel Corrosion in Oil-Well Acidizing: Experimental and Computational Insights - Mohammad Salman; Srivastava V.; Quraishi M.A.; Chauhan D.S.; Ansari K.R.; Haque J. (My University, 2025)
Abstract: Three quinoline derivatives as corrosion inhibitors for N80 steel 15% HCl solutions. Influence of the –H, –OCH3 groups and the introduction of π bonding are reported in the present report. Experimental studies were performed using gravimetric tests, electroanalytical methods, and surface analysis. The cinnamaldehyde derivative displayed the maximum inhibition efficiency of 95% at 300 mg L–1, followed by the –OCH3 and the –H derivatives. The inhibitor adsorption on the metal surface obeyed the Langmuir isotherm with a mixed mode of physical and chemical adsorption. Impedance measurements revealed an increase in the charge transfer resistance with the addition of increasing inhibitor dosage, which supported the inhibitor adsorption. Frequency modulations displayed a lowering in the corrosion current density upon the addition of the corrosion inhibitors. Polarization studies revealed that all the three inhibitors showed a mixed-type inhibition behavior with cathodic prevalence. SEM and FTIR of the inhibitor-adsorbed steel surface affirmed the adsorption of inhibitor and improvement in the surface smoothness of the N80 steel. The pKa analysis revealed that all the three inhibitors undergo protonation at the pyridine Nitrogen at the experimental pH. The DFT studies showed that the protonated form of the inhibitors is more active compared to the neutral form. © 2021, Pleiades Publishing, Ltd.